2020
DOI: 10.3389/fped.2020.00238
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Post-hemorrhagic Ventricular Dilatation: A Multiple-Treatment Meta-Analysis

Abstract: Objective: To perform a systematic review and multiple-treatment meta-analysis for the treatment of premature infants with post-hemorrhagic ventricular dilatation (PHVD), to prevent death or long-term neuro-disability. Design/Method: A systematic review was performed using PubMed, EMBASE, and the Cochrane Library. A free-word search was performed to identify likely relevant literature intervention trials of PHVD in preterm infants. Initially, network mapping was performed followed by performing a Bayesian rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Most studies reporting VPS rates only evaluated patients who received neurosurgical consultation or intervention, which limits comparison across studies because treatment thresholds vary 38. Previous meta-analyses have compared outcomes by surgical treatment modality,39–41 but the current study is the first to report pooled estimates of shunting of all infants diagnosed with IVH regardless of need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reporting VPS rates only evaluated patients who received neurosurgical consultation or intervention, which limits comparison across studies because treatment thresholds vary 38. Previous meta-analyses have compared outcomes by surgical treatment modality,39–41 but the current study is the first to report pooled estimates of shunting of all infants diagnosed with IVH regardless of need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of every included study was assessed by SLY with respect to selection (randomisation and concealment bias), measurement (performance bias, blinding of radiologist), attrition (loss to follow-up) and reporting bias, based on the Cochrane Handbook for Systematic Reviews (31) and previous studies (11). A study's risk of bias was assessed as low, high, or unclear.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…(5,6) These can lead to long-term adverse outcomes such as cerebral palsy, developmental delay, visual, hearing impairment, (7)(8)(9), and death, (10) meaning that IVH and its complications are one of the leading causes of neurological disability and mortality for premature infants. (2,8,11) Preventative strategies have been based on the pathogenesis of IVH, which is predominantly due to the immaturity and fragility of the germinal matrix vasculature. (3,12) Disturbances of cerebral blood flow and impaired cerebral autoregulation can damage fragile blood vessels in the germinal matrix, causing them to bleed.…”
Section: Introductionmentioning
confidence: 99%
“…These results represented the most marked improvement in cognition and survival with any intervention after IVH and PHVD. A study that used network meta-analysis methodology to evaluate the outcome of ten different trials for PHVD also demonstrated that DRIFT is the most efficacious and the most likely treatment to improve outcomes [44]. Despite this, however, the DRIFT technique has not been widely adopted and has not changed standard practice due to the resource-intensive nature of the treatment and the potential risks of secondary haemorrhage.…”
Section: Management Of the Blood And Breakdown Productsmentioning
confidence: 99%
“…Further research into the direct management of intraventricular blood and its breakdown products is required. Despite the incidence and developmental impact of IVH and PHVD, only about 700 infants have been enrolled into intervention trials, and fewer than 500 have had long-term developmental measures reported [44]. The role of surgical and medical therapies in removing the blood and reducing its toxicity on the developing brain requires robust evaluation and may hold the potential to further improve developmental outcomes in premature neonates with IVH.…”
Section: Future Directionsmentioning
confidence: 99%